The importance of positive leadership in the process of change on the example of the banking sector - Mieczysław Morawski; Lidia Jabłonowska-Luba (Foundations of Management, 2021)
In today's world, the success of modern company in dealing with change depends, to a large extent, on a positive approach toward its knowledge workers. The aim of the present study is to indicate the significance of positive leadership in the implementation of crucial changes in an organization in the environment of knowledge workers. The study has researched the case of a major Polish bank undergoing significant change in the Risk Management Division. Presented research covers the period between 2013 and 2019 and was conducted thanks to the participation of nearly 600 employees. Changes in the level of their engagement were systematically studied. All ten leaders in the division were also investigated, so that ten individual Reiss Motivation Profile (RMP) profiles could be created. Study results have confirmed that team leaders possess characteristics that confirm their preferred style is positive leadership, with a clear servant leadership attitude. The formulated hypotheses have been positively verified. It has been confirmed that the orientation of leaders on positive leadership ensured an effective implementation of crucial changes in the environment of knowledge workers.
Keywords: M; M1; M12; M120; 650; positive leadership; process of change; knowledge worker; banking sector